BIOECONOMY IN THE EUROPEAN UNION. ANALYSIS OF KEY STRATEGIES AND INDICATORS - Branza, Gratiela (Ecoforum Journal, 2022)
A new concept promoted in the European Union, the bioeconomy, can contribute to sustainable economic growth, which respects the environment and promotes renewable resources. The transition to a sustainable economy, supported by bio principles is based on technology, economic profitability and awareness by members of society. This paper addresses this concept and analyzes the European Union's strategy in the field of bioeconomy and funding instruments to achieve this goal. The paper also presents a brief analysis of the indicators that allows the monitoring of the bioeconomic sectors from the economic, social and environmental point of view. The bioeconomy must become a reality in every Member State of the European Union.